2021
DOI: 10.1111/ans.16966
|View full text |Cite
|
Sign up to set email alerts
|

Is pathological complete response predictable after neoadjuvant chemotherapy in breast cancer? A single institution's retrospective experience

Abstract: Background: Pathological complete response (pCR), in breast cancers, after neoadjuvant chemotherapy is linked to improved survival. Determining complete response to chemotherapy prior to surgery has remained elusive even using a combination of pathological factors and imaging modalities, making surgery still a necessity. Methods: A retrospective analysis was performed from a single institution from 2013 to 2018. Breast cancer patients treated with neoadjuvant chemotherapy with pre-and postchemotherapy magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Breast cancer is a heterogeneous tumor. Different pathological indicators and clinical features of breast cancer patients often mean different sensitivity of neoadjuvant chemotherapy and survival prognosis [21]. This study found that neoadjuvant chemotherapy e cacy and survival prognosis in breast cancer patients were correlated with TNM staging, breast cancer tissue sex hormone receptor, Ki-67 expression and neoadjuvant chemotherapy, but not related to age, body mass index, neoadjuvant chemotherapy cycle, pCR and the expression of Her-2.…”
Section: Discussmentioning
confidence: 67%
“…Breast cancer is a heterogeneous tumor. Different pathological indicators and clinical features of breast cancer patients often mean different sensitivity of neoadjuvant chemotherapy and survival prognosis [21]. This study found that neoadjuvant chemotherapy e cacy and survival prognosis in breast cancer patients were correlated with TNM staging, breast cancer tissue sex hormone receptor, Ki-67 expression and neoadjuvant chemotherapy, but not related to age, body mass index, neoadjuvant chemotherapy cycle, pCR and the expression of Her-2.…”
Section: Discussmentioning
confidence: 67%